Micro-Sphere of Shayṭānic Influence in the Qur’ān: Human Life and Divine Testing - Balaraj Saraf (LECTURES: Journal of Islamic and Education Studies, 2026)
This study examines the Qur’ānic concept of Shayṭānic influence at the micro-cognitive level and its role in the divine testing of human beings. The Qur’ān presents human life as a purposeful moral examination (Qur’an 67:2), wherein Shayṭān is granted limited psychological access described as waswasah (Qur’an 7:20; 20:120). This influence operates only when human consciousness momentarily disengages from revelation, allowing distorted suggestions to affect moral perception and reasoning (Qur’an 2:268; 14:22). The Qur’ān restricts this influence through explicit divine command, emphasizing that Satan has no authority over sincere servants (Qur’an 15:42). Through thematic textual analysis, this paper argues that the Qur’ānic worldview frames human success as dependent on continuous remembrance of Allah, adherence to revelation, and resistance to fleeting internal disruptions (Qur’an 16:98–100; 7:201). The study concludes that the micro-sphere of Shayṭānic influence serves as a calibrated mechanism for revealing sincerity, strengthening spiritual vigilance, and fulfilling the divine purpose of human existence.